(untitled) (Research, Society and Development, 2024)
Wind power, an increasingly widespread renewable source of electrical energy, faces a significant challenge: the variability in generation caused by the intermittency of wind patterns. This intermittency is characterized not only by seasonal fluctuations but also by daily variations, significantly impacting the ability to predict and support an electrical system using this energy source. Daily intermittency is the main reason for reductions in wind generation, known as “curtailment” or “constrained-off”. These reductions occur when there is low demand within the National Interconnected System (SIN) or when generation exceeds the throughput capacity of transmission lines. The objective of this study is to demonstrate the feasibility of converting excess wind energy, often wasted through curtailments, into green hydrogen. Using data taken from a survey of ONS documents. By using an existing primary energy source, this approach minimizes the initial investment required for fuel production. The manufactured fuel can then be stored and used during periods of low generation due to wind intermittency or when system demand requires it. The results indicate that in 2023 alone, in the state of Ceará – Brazil, a single wind farm could produce over 2,000 tons of green hydrogen, using energy that would otherwise be wasted.